Effects of Prefrontal Transcranial Direct Current Stimulation and Motivation to Quit in Tobacco Smokers: A Randomized, Sham Controlled, Double-Blind Trial - Vitor de Souza Brangioni, Maria C.; Pereira, Danilo A.; Thibaut, Aurore; Fregni, Felipe; Brasil-Neto, Joaquim P.; Boechat-Barros, Raphael (Frontiers in Pharmacology, 2018)
Abstract Transcranial direct current stimulation (tDCS) applied over the dorsolateral prefrontal cortex (DLPFC) has been shown to reduce cravings in tobacco addiction; however, results have been somewhat mixed. In this study, we hypothesized that motivation to quit smoking is a critical factor of tDCS effects in smokers. Therefore, we conducted a double-blind, randomized clinical trial to evaluate the effects of both tDCS and motivation to quit on cigarette consumption and the relationship between these two factors. DLPFC tDCS was applied once a day for five days. Our primary outcome was the amount of cigarettes smoked per day. We collected this information at baseline (d1), at the end of the treatment period (d5), two days later (d7) and at the 4-week follow-up (d35). Visual Analog Scale (VAS) for motivation to quit was collected at the same time-points. 36 subjects (45±11years old; 24.2±11.5 cigarettes daily smoked; 21 women) were randomized to receive either active or sham tDCS. In our multivariate analysis, as to take into account the mediation and moderation effects of motivation to quit, we found a significant main effect of tDCS, showing that tDCS was associated with a significant reduction of cigarettes smoked per day. We also showed a significant interaction effect of motivation to quit and treatment, supporting our hypothesis that tDCS effects were moderated by motivation to quit, indicating that higher levels of motivation were associated with a larger tDCS response. We found that the participants’ motivation to quit alone, both at baseline and at follow-up, does not explain the decrease in the average cigarette consumption. Repetitive prefrontal tDCS coupled with high motivation significantly reduced cigarette consumption up to 4-weeks post-intervention.